UPAYA MENINGKATKAN HASIL BELAJAR PKn MENGGUNAKAN MODEL ACTIVE LEARNING TIPE ROLE REVERSAL QUESTION PADA SISWA KELAS VI SD N 013 BATU LANGKAH KECIL KECAMATAN KUOK TAHUN 2021 - Eliana (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
This study aims to describe the improvement of Civics learning outcomes by using an active learning model of the role reversal question type in class VI SD N 013 Batu Step Kecil Kuok District.This type of research is classroom action research. The research subjects were the sixth grade students of SD N 013 Batu Step Kecil, totaling 36 students. Methods of data collection in this study using tests, observation and documentation. Research instruments in the form of tests and observation sheets. The data analysis technique used is descriptive quantitative and qualitative. The indicator for the success of the action is marked by 75% of the number of students who take part in the learning process has obtained a score of 70.The results showed an increase in Civics learning outcomes for fifth grade students of SD N 013 Batu Step Kecil after using the active learning model type role reversal question in both cycle I and cycle II. In the first cycle, students who scored 70 increased by 25% with the initial condition of 44% increasing to 69% and in the second cycle it increased by 28% to 97%. The average value of learning outcomes in the first cycle increased by 8.75% with the initial condition of 66.53 increasing to 75.27 and in the second cycle it increased by 10.97% to 86.25.